Influence Of Price And Product Quality On Customer Satisfaction (Case Study at the Obela Store in Bengkulu City) - Subandrio Subandrio; M. Prawiro Putra Arizahan (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the effect of price and product quality on consumer satisfaction (a case study at the Obela Store, Bengkulu City). This type of research uses a quantitative descriptive research method. The population used in this study are consumers who shop at the Obela Store in Bengkulu City. The number of respondents in this study were 70 people. The data collection method uses a questionnaire and uses analytical techniques using multiple linear regression analysis tests and hypothesis testing, namely the t test and f test. Based on the results of multiple linear regression, the regression equation Y = 2.828 + 0.924 (X1) + 0.077 (X2) and the results of the t test and f test of this study can be concluded that price has a significant effect on consumer satisfaction, this is evidenced by the results of the t test showing the value of t_hit >t_table (9.370 > 1.668) and (sig α = 0.00 <0.05). This means H_0 is rejected and H_a is accepted. Product quality has a significant effect on consumer satisfaction, this is evidenced by the results of the t test showing the value of t_hit>t_table (2.032> 1.668) and (sig α = 0.03 <0.05). This means H_0 is rejected and H_a is accepted. Price (X_1) and product quality (X_2) together have a significant effect on consumer satisfaction (Y) at the Obela Store Bengkulu City, this is evidenced by the F test showing the value of F_count>F_table, namely (83,604 > 2.38